Abnormal epithelial structure and chronic lung inflammation after repair of chlorine-induced airway injury - Mo, Yiqun (Am J Physiol Lung Cell Mol Physiol, 2014)
Chlorine is a toxic gas used in a variety of industrial processes and is considered a chemical threat agent. High-level chlorine exposure causes acute lung injury, but the long-term effects of acute chlorine exposure are unclear. Here we characterized chronic pulmonary changes following acute chlorine exposure in mice. A/J mice were exposed to 240 parts per million-hour chlorine or sham-exposed to air. Chlorine inhalation caused sloughing of bronchial epithelium 1 day after chlorine exposure, which was repaired with restoration of a pseudostratified epithelium by day 7. The repaired epithelium contained an abnormal distribution of epithelial cells containing clusters of club or ciliated cells rather than the uniformly interspersed pattern of these cells in unexposed mice. Although the damaged epithelium in A/J mice was repaired rapidly, and minimal airway fibrosis was observed, chlorine-exposed mice developed pneumonitis characterized by infiltration of alveoli with neutrophils and prominent, large, foamy macrophages. Levels of CXCL1/KC, CXCL5/LPS-induced CXC chemokine, granulocyte colony-stimulating factor, and VEGF in bronchoalveolar (BAL) fluid from chlorine-exposed mice showed steadily increasing trends over time. BAL protein levels were increased on day 4 and remained elevated out to day 28. The number of bacteria cultured from lungs of chlorine-exposed mice 4 wk after exposure was not increased compared with sham-exposed mice, indicating that the observed pneumonitis was not driven by bacterial infection of the lung. The results indicate that acute chlorine exposure may cause chronic abnormalities in the lungs despite rapid repair of injured epithelium.